2019
DOI: 10.1111/jgh.14938
|View full text |Cite
|
Sign up to set email alerts
|

A meta‐analysis on small intestinal bacterial overgrowth in patients with different subtypes of irritable bowel syndrome

Abstract: Background Enteric microbiota is increasingly being recognized as an important factor in the pathogenesis of irritable bowel syndrome (IBS). The reported prevalence of small intestinal bacterial overgrowth (SIBO) in subjects with IBS is highly variable, and there is no consensus on the role of SIBO in different subtypes of IBS, and indications and methods of testing. Methods A comprehensive literature search was performed for studies applying tests for SIBO in subjects with IBS. After applying prospectively de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 65 publications
1
27
0
1
Order By: Relevance
“…Most studies found an association between SIBO diagnosed by quantitative upper gut aspirate culture, glucose and lactulose HBTs and IBS 26 . In a recent meta‐analysis, we found that the relative risk of SIBO among patients with IBS versus control using glucose HBT was 4.234 (95% confidence interval 3.015–5.947), and it was greater among patients with IBS‐D than other subtypes of IBS 26 …”
Section: Gut Microbiota Dysbiosis In Irritable Bowel Syndromementioning
confidence: 76%
“…Most studies found an association between SIBO diagnosed by quantitative upper gut aspirate culture, glucose and lactulose HBTs and IBS 26 . In a recent meta‐analysis, we found that the relative risk of SIBO among patients with IBS versus control using glucose HBT was 4.234 (95% confidence interval 3.015–5.947), and it was greater among patients with IBS‐D than other subtypes of IBS 26 …”
Section: Gut Microbiota Dysbiosis In Irritable Bowel Syndromementioning
confidence: 76%
“…Chronic enteropathies (CE) are a frequent and frustrating cause of illness in dogs [ 1 ], defined as persistence of gastrointestinal symptoms such as vomiting and diarrhoea for three or more weeks. In humans and in dogs, both chronic and acute enteropathies exhibit imbalanced composition of intestinal microbiota, defined as dysbiosis, which has been recognized as a major player in the development of these diseases [ 2 , 3 , 4 , 5 , 6 ]. Moreover, as previously reported, CE are characterized by decreased faecal bacterial diversity and richness [ 7 ] with possible impact on the primary functions of gut microbiota.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies found a strong association between the IBS and SIBO. A meta‐analysis showed a higher relative risk of the SIBO among IBS patients compared with controls 25 . A recent study on patients presenting with bloating, abdominal pain, or diarrhea, thought to be suffering from SIBO, found alterations in small intestinal microbial composition 26 .…”
Section: Pathophysiological Mechanisms Of Fgids With Special Emphasis On Gut Microbiota Dysbiosismentioning
confidence: 98%
“…A meta‐analysis showed a higher relative risk of the SIBO among IBS patients compared with controls. 25 A recent study on patients presenting with bloating, abdominal pain, or diarrhea, thought to be suffering from SIBO, found alterations in small intestinal microbial composition. 26 Another study showed a significant reduction of the anaerobic genera Veillonella , Prevotella , and Actinomyces in the duodenal mucosal biopsies from patients with FD compared with healthy controls.…”
Section: Pathophysiological Mechanisms Of Fgids With Special Emphasis On Gut Microbiota Dysbiosismentioning
confidence: 99%